2018
DOI: 10.1021/acsami.8b04386
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interconnected Porous Networks of NiCo Disulfide as Efficient Bifunctional Electrocatalysts for Overall Water Splitting

Abstract: Electrochemical splitting of water has been viewed as a highly efficient technique to produce clean hydrogen and oxygen energy. However, designing inexpensive multifunctional electrocatalysts with high performance is a great challenge. Here, a unique three-dimensional catalyst of self-interconnected porous Ni-Co disulfide networks grown on carbon cloth [(NiCo)S nanowires (NWs)/CC] was prepared by a facile hydrothermal method coupled with further low-temperature sulfuration strategy. As a bifunctional electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…S14a). Although the Co and O of MOF-driven CoS 2 after OER durability test were uniformly distributed, signal of S was relatively weak due to the formation of surface CoOOH 54 . XPS analysis was conducted (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S14a). Although the Co and O of MOF-driven CoS 2 after OER durability test were uniformly distributed, signal of S was relatively weak due to the formation of surface CoOOH 54 . XPS analysis was conducted (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…S14b–d). The peak of CoOOH (783 eV) was observed in Co 2p spectrum 54,55 . In S 2p spectrum, only S-O peaks were featured 6,56 .…”
Section: Resultsmentioning
confidence: 97%
“…[8,9] Therefore, exploring highly efficient, earth-abundant, and stable catalysts is vital for facilitating the development of electrocatalysis. Among the multitudinous reported catalysts, 3D transition metal-based catalysts (including phosphides, [10][11][12] sulfides, [13][14][15] nitrides, [16][17][18] borides, [19][20][21] (oxy)hydroxides, [22] and so on) have been explored as potential alternatives for the half reactions of water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Besides the intrinsic activity, the performance of FeS 2 catalyst also depends on the density of active sites. [16] Designing nanostructures like nanowires, nanosheets and nanorods is considered to be an effective method to expose more active sites of a catalyst. [17][18][19] Among various nanostructures, zero-dimensional (0D) nanoparticles (NPs) enable maximum exposure of active sites due to their ultra-small size and large number of coordinatively unsaturated sites, thus significantly improving the HER activity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cobalt (Co) doping significantly elevated the Fermi level of FeS 2 , and facilitated electron transfer from the FeS 2 surface to H, thereby granting it with higher HER activity . Besides the intrinsic activity, the performance of FeS 2 catalyst also depends on the density of active sites . Designing nanostructures like nanowires, nanosheets and nanorods is considered to be an effective method to expose more active sites of a catalyst .…”
Section: Introductionmentioning
confidence: 99%